Wage sale and purchase practices among agricultural workers in Curup, Bengkulu: A Maqasid of Shariah perspective on economic justice and wealth protection‎ - Arifin, Rahman; Syaputra, Ahmad Danu; Triyanto, Andi; Muharir, Muharir; Saifudin, Ahmad; Samawi, Mohammad Wirmon; Yudha, Ana Toni Roby Candra (Universitas Islam Indonesia, 2025)
IntroductionWage trading, a practice where agricultural workers sell their future wages before receiving them—often at a reduced value—has become prevalent in the farming communities of Curup, Bengkulu. Although rooted in mutual agreement, this system raises critical ethical and legal questions regarding its alignment with Islamic economic principles, especially those outlined in the framework of Maqashid Shariah, which emphasizes justice and the protection of property.ObjectivesThis study aims to analyze the wage sale and purchase system through the lens of Maqashid Shariah, particularly focusing on whether such practices fulfill the objectives of wealth protection and social justice or contribute to economic exploitation and uncertainty among vulnerable workers.MethodUsing a qualitative case study approach, this research collected primary data through interviews with agricultural workers engaged in wage trading in Curup, Rejang Lebong, and Bengkulu. Secondary data were obtained from Islamic jurisprudence literature on Maqashid Shariah. The analysis applies the five core principles of Maqashid Shariah to evaluate the implications of deferred wage payments and wage sales.ResultsFindings indicate that although wage deferral is seen as a cooperative tradition, it often places workers at risk of financial instability, compelling them to sell their wages at unfair prices. This practice undermines the principle of property protection (hifz al-mal) and the protection of life (hifz an-nafs). It also contradicts the ideals of justice and welfare that Maqashid Shariah promotes. The study emphasizes that the presence of mutual consent does not automatically legitimize practices that may harm the economically disadvantaged.ImplicationsThe analysis suggests that reforms are needed to make wage systems more just and compliant with Islamic economic values. These include timely wage payments and the provision of Sharia-based financial alternatives to prevent exploitation. Educating communities about their economic rights within the Maqashid framework can also foster more ethical labor practices.Originality/NoveltyThis study contributes a unique perspective by applying Maqashid Shariah to assess the socio-economic impact of wage trading. It addresses a rarely examined issue in Islamic economic discourse and offers practical recommendations to bridge the gap between traditional practices and Islamic legal objectives.